Homem imaginativo e homem de ação na constituição do imperium em Benedictus de Spinoza - Lima, Francisca Juliana Barros Sousa (2024)
The writings of Benedictus de Spinoza (1632-1677) reflect, among other things, on human action, freedom and happiness. These reflections have implications in the political sphere. From the social genesis of imperium, we will analyze the role of reason in conjunction with the notions of happiness and freedom (through simultaneous plurality). In other words, the objective of this research concerns the role of reason in the movement of constitution of imperium and in the dynamics of increasing men's power to think and act. To this end, we will resort to the main indications given by the modern philosopher regarding reality in order to think about finite modes as determined expressions of God's power. Finite modes are, at the same time, effects and producers of effects. Based on these considerations, we will advance on the genesis of human affective dynamics and its developments in the formation of the political. Given this scenario, we ask the following questions: what is the dynamic that underlies the movement that makes a man associate with others? Is it possible to think of a relationship and/or simultaneity between passionate experience and the development of a rational dynamic concerning the constitution of the political body? Does reason have any role in this process? How can happiness and freedom be experienced by men in view of the formation of the political and the rational dynamic? To investigate these issues, we will analyze the theses presented by Spinoza, mainly in Ethics (E), Theological-Political Treatise (TTP), and Political Treatise (TP). Reason will be the guiding thread regarding the formation of the imperium and the experience of freedom and happiness.